2022
DOI: 10.1101/2022.12.15.520449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gba1 deletion causes immune hyperactivation and microbial dysbiosis through autophagic defects

Abstract: Mutations in the GBA1 gene cause the lysosomal storage disorder Gaucher disease (GD) and are the greatest genetic risk factor for Parkinson disease (PD). Communication between gut and brain and immune dysregulation are increasingly being implicated in neurodegenerative disorders such as PD. Here, we show that flies lacking the Gba1b gene, the main fly orthologue of GBA1, display widespread innate immune up-regulation, including gut inflammation and brain glial activation. We also demonstrate gut dysfunction in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Alternatively, GlcCer accumulation in macrophages could cause hyperreactivity to normal immune stimuli, as previously reported in macrophages from PD patients with GBA mutations [15]. Atilano et al [26] partially addressed this possibility by raising GCase-deficient flies in germ-free conditions. The improvements in lifespan and climbing after this intervention, however, were modest compared to those seen when we restored GCase activity in activated macrophages.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Alternatively, GlcCer accumulation in macrophages could cause hyperreactivity to normal immune stimuli, as previously reported in macrophages from PD patients with GBA mutations [15]. Atilano et al [26] partially addressed this possibility by raising GCase-deficient flies in germ-free conditions. The improvements in lifespan and climbing after this intervention, however, were modest compared to those seen when we restored GCase activity in activated macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…The major humoral immune pathways in mammals, including Toll, NF-κB/Imd, and JAK/STAT, are conserved in Drosophila [21, 22], and Drosophila blood cells (hemocytes) are a well-validated model for macrophages and other human myeloid immune cells [23, 24]. In addition, Drosophila studies have shown the same association between GCase deficiency and immune system activation that is seen in mammals [25, 26]. We therefore used the Gba1b mutant to determine which components of the immune system contribute to the neuropathology associated with GCase deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Both single and double KO flies presented lysosomal defects, progressive age-dependent locomotor deficits, a seven-fold increase in the amount of C16:0 GlcCer in comparison to age-matched controls, autophagic deficits in their brains, synaptic loss and neurodegeneration. Recently, Atilano et al used this Gba1b KO model to study immune and gut pathologies and noticed that these flies had upregulated inflammation, gut dysfunction (increased intestinal transit time, gut barrier permeability, and microbiome dysbiosis), and glial activation in the brain [135].…”
Section: Ko Drosophila Modelsmentioning
confidence: 99%